Can Te Reo Māori Survive the 21st Century? An Index-Linked Approach to Indigenous Language Revitalisation - Moon, Paul (Te Kaharoa, 2022)
In 2017, I published a book called Killing Te Reo Māori.  It was not especially well received at first, with some reviewers condemning it, oddly, without ever having read the work (and admitting as much). One academic even publicly denounced the book solely on the basis that she was unable to find the website of the photographer who produced one of the imagesfor the cover (the details were later provided to her). This sort of interminable barrel-scraping was indicative of how some critics latched onto the shadow rather than the substance of the work.Had these critics paid attention to the text instead of prejudging it, they would have realised that the book was not what they imagined – that is, a criticism of the language. Rather, it was a pointed critique of many of the attempts at revitalising the Te Reo – attempts that seem to be failing with depressing regularity (a fact that was confirmed in subsequent research on the topic). Indeed, the regularity is such that I began making predictions every year that around Māori Language Week, a new book, a new method of teaching, or a new app would be revealed, and that it would promise to contribute – often in a ‘ground-breaking’ way – to saving Te Reo. I also predicted that the promotion would be considerable, the execution uncertain, and the evaluation nonexistent. This prophecy has played out every year, and in the meantime, the erosion of Te Reo as a living language proceeds towards its terminal end.